(untitled) (Academicia Globe: Inderscience Research, 2024)
Hypertrophic gingivitis, characterized by abnormal enlargement of gingival tissues, poses a significant challenge in dental practice. Modern treatment options encompass both non-surgical and surgical modalities, each with its own set of advantages and disadvantages. Non-surgical interventions, including oral hygiene measures, pharmacotherapy, and laser therapy, offer minimally invasive approaches for managing gingival inflammation. Surgical modalities such as gingivectomy and gingivoplasty provide more definitive solutions for reshaping and recontouring gingival tissues but may be associated with postoperative complications. Adjunctive therapies, including periodontal maintenance therapy and patient education, play a crucial role in preventing disease recurrence and promoting long-term periodontal health. By understanding the advantages and disadvantages of these treatment modalities, dental professionals can tailor their approach to care to meet the individual needs of each patient, ultimately promoting optimal periodontal health and enhancing the overall patient experience.